Analisis Ketimpangan Pendapatan antar Wilayah di Kawasan Kedungsepur, Barlingmascakeb, dan Subosukawonosraten Periode 2008-2017 - Viana Dwi Waluyaningsih; Achma Hendra Setiawan (Universitas Diponegoro, 2020)
Kedungsepur, Barlingmascakeb, and Subosukawonosraten areas are Strategic Areas that are contained in the Central Java's RTRW in 2009-2029. The economic growth of Kedungsepur, Barlingmascakeb, and Subosukawonosraten as a whole continued to increase from 2008-2017. The economic growth difference in each region in Kedungsepur, Barlingmascakeb, and Subosukawonosraten indicates an imbalance in regional income. This study aims to analyze the level of regional income inequality in the Kedungsepur, Barlingmascakeb, and Subosukawonosraten regions, determine the classification of development between the three regions, as well as the causality relationship between economic growth variables and the level of inequality in the three regions and prove the Kuznets Hypothesis. The analytical method used is the Williamson Index analysis, Klassen Typology, Granger Causality Test, and Regression Curve Estimation. The results of this study indicate that the highest level of regional income inequality is the Barlingmascakeb area Williamson Index value 0.75 while the most evenly distributed region is the Subosukawonosraten the Williamson Index value is only 0.37. And there are some areas where the development is lagging behind. For granger causality test results only occured in the Kedungsepur region because between the both variables inequality and economic growth have a less than 0.05 probability value. Whereas the Kuznets Hypothesis is also only proven in the Subosukawonosraten region with an inverted U-shaped curve.